Increasing Learning Motivation by Using a Smartphone: An Empirical Study in Elementary School - Stevanus, Ivan; Purwanta, Edi; Suwarjo, (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to provide empirical evidence about patterns of social interaction between elementary school students and the impact of gadget usage. This research is descriptive research with a survey method. The research sample was taken by purposive sampling. This study involved 475 students from four elementary schools in Yogyakarta consisting of 234-second grade students and 241 fifth grade elementary school students. Data collected, tabulated, analyzed, and conclusions. The final result shows a pattern of social interaction in the use of gadgets has two patterns, namely associative and dissociative. The contribution of this research is to determine the interaction patterns that influence the use of gadgets among elementary school students in Indonesia